Downregulation of striatin leads to hyperphosphorylation of MAP2, induces depolymerization of microtubules and inhibits proliferation of HEK293T cells. Issue 2 (10th December 2014) - Kaźmierczak-Barańska, Julia; Pęczek, Łukasz; Przygodzka, Patrycja; Cieślak, Marcin J.
Abstract : Microtubules are tubular polymers of α/β‐tubulin that are involved in the maintenance of cell shape, motility, and intracellular transport and in the segregation of chromosomes during cell division. Microtubules are dynamic structures, and their assembly is regulated by phosphoproteins called microtubule‐associated proteins (MAPs). We propose that striatin, a protein belonging to the striatin family of proteins, is involved in regulation of microtubules. In HEK293T cells, striatin colocalizes with microtubules and stably associates with PP2Ac. Inhibition of striatin expression results in hyperphosphorylation of MAP2 and destabilizes microtubules. Striatin‐induced destabilization of microtubules inhibited the proliferation of HEK293T cells and caused the accumulation of cells in the G0/G1 phase of the cell cycle. These results suggest that the PP2A/striatin complex modulates microtubule dynamics by regulating MAP2 phosphorylation. Abstract : Striatin colocalizes with microtubules and stably associates with PP2Ac. Striatin is involved in regulation of MAP2 phosphorylation. Downregulation of striatin inhibits proliferation of HEK293T cells. Inhibition of striatin results in accumulation of cells in the G0/G1 phase of the cell cycle. PP2A/striatin complex modulates microtubule dynamics.